Experimental and numerical investigations on the effect of a novel internal surface micro grooving towards improving convective heat transfer performance of tube heat exchangers - Abdehalim Ahmed Eid, Mohamed Moustafa; Mohd Nashrul, Mohd Zubir; Muhammad, Mohd Ridha; Md. Salim Newaz, Kazi; Mt Aznam, Suazlan; Md Mehedy, Hasan Rony; Ibrahim, F. A.; Alam, Md Shadab; Sadri, Rad (AIP Publishing, 2023)
In the present work, the use of the passive heat transfer enhancement technique through surface alteration was explored. The enhancement was achieved through internal conduit surface microgrooving using a new apparatus that was developed by modifying a Magnetic Abrasive Finishing technique. A new surface profile was created and later verified using optical and laser profiler measurement. The new profile was investigated numerically to compare the heat transfer and hydrodynamic performance against other profiles that have been studied in the literature. It was found from the results that the new profile shows much higher heat transfer improvement and comparable pressure loss to the previously investigated profiles (i.e. square, rectangular, trapezoidal and circular). Overall, the new groove geometry provides the highest performance followed by the circular, triangular, curvy, square and rectangular grooves. Also, the results indicate that designs with a smooth profile performs better than those with sharp edges, owing to the elimination of stationary fluid spots within the grooves. The effectiveness between the profiles was compared based on the level of heat transfer enhancement against the flow penalty. Experimental validation was further conducted for the experimentally generated groove. The results revealed that a relatively small surface temperature drop was obtained, corresponding to a slight improvement in heat transfer. This confirms the results generated by the simulation that groove size plays a major role in attaining significant improvement in heat transfer